Exosomes Represent an Immune Suppressive T Cell Checkpoint in Human Chronic Inflammatory Microenvironments. - Shenoy, Gautam N (Immunol Invest, 2020)
BACKGROUND: T cells present in chronic inflammatory tissues such as nasal polyps (from chronic rhinosinusitis patients) have been demonstrated to be hypo-responsive to activation via the TCR, similar to tumor-specific T cells in multiple different human tumor microenvironments. While immunosuppressive exosomes have been known to contribute to the failure of the tumor-associated T cells to respond optimally to activation stimuli, it is not known whether they play a similar role in chronic inflammatory microenvironments. In the current study, we investigate whether exosomes derived from chronic inflammatory microenvironments contribute to the immune suppression of T cells. METHODS: Exosomes were isolated by ultracentrifugation and characterized by size and composition using nanoparticle tracking analysis, scanning electron microscopy, antibody arrays and flow exometry. Immunosuppressive ability of the exosomes was measured by quantifying its effect on activation of T cells, using nuclear translocation of NFκB as an activation endpoint. RESULTS: Exosomes were isolated and characterized from two different types of human chronic inflammatory tissues - nasal polyps from chronic rhinosinusitis patients and synovial fluid from rheumatoid arthritis patients. These exosomes arrest the activation of T cells stimulated via the TCR. This immune suppression, like that which is seen in tumor microenvironments, is dependent in part upon a lipid, ganglioside GD3, which is expressed on the exosomal surface. CONCLUSION: Immunosuppressive exosomes present in nonmalignant chronic inflammatory tissues represent a new T cell checkpoint, and potentially represent a novel therapeutic target to enhance the response to current therapies and prevent disease recurrences.